Adaptação transcultural do instrumento The Flow State Scale for Occupational Task (FSSOT) - Ramos, Luis Paulo Alves (2024)
Introduction: The use of Occupational Therapy instruments in Brazil that measure engagement in meaningful occupations is still scarce. Flow is a mental state in which there is harmony between consciousness and the activity performed, thus achieving happiness through control of inner life. Objective: To carry out the translation, back-translation and evaluation stages of the expert committee of the instrument The Flow State Scale for Occupational Tasks (FSSOT), for the Portuguese language (Brazil). Methodology: The stages of cross-cultural adaptation carried out were based on two documents, namely: Guidelines for the Process of Cross-Cultural Adaptation of Self- Report and in the Report of the ISPOR Task Force for Translation and Cultural Adaptation. The present steps were carried out with the approval of the instrument's author. Results: The instrument was broken down into 20 sentences and during the translation, 16 discrepancies were identified between the translators. After analysis, 11 sentences (55%) from T-1 were chosen and 5 sentences (25%) were chosen for the translation of T-2. In the back-translation, discrepancies were found in 15 sentences, with 11 sentences being chosen (73.36%) from the RT-2, two sentences (13.32%) from the T-2 translation, and the remaining two sentences (13.32%), it was decided to combine the two back-translations. In the Expert Committee, 07 sentences presented an agreement level below 80%. Of these, 3 sentences (42.85%) obtained an agreement level below 80% in conceptual equivalence (ECO), 2 sentences (28.57) corresponded below 80% in semantic equivalence (ES) and in terms of cultural equivalence (ECU), only 2 sentences (28.57) corresponded below 80%. After submitting the instrument to the authors, the phrase “It took me a significant amount of time to complete the activity.” Accordingly, the item asks how significant the activities carried out were and not about the time spent performing them. Discussion: All steps carried out faithfully followed the manuals that provide guidance on cross-cultural adaptation, requiring a pre-test to complete the cross-cultural adaptation process of the State of Flow Scale for Occupational Performance for Brazil. This conclusion will contribute to filling the gap regarding the Flow perspective within the clinical practice of Occupational Therapy.